Race and vocational education and training in England - Avis, James [Verfasser]; Orr, Kevin [Verfasser]; Warmington, Paul [Verfasser] (My University, 2017)
"Black and minority ethnic students (BME) are a significant constituency in vocational education and training (VET) and FE in England. Despite this recent research on race and VET has become a marginal concern. Insofar as current VET research addresses social justice, race appears to be a supplementary concern. Although there is a substantial literature addressing race and education, this focuses primarily on schools and higher education. This paper examines why there is a need to develop a research agenda that analyses participation, outcomes and experiences of BME VET students, particularly those on 'non-advanced' programmes (equivalent to European Qualification Framework Level 1-3) with uncertain labour market outcomes and who are arguably being 'warehoused' in low status courses. The paper reflects on the historically specific reasons for the dearth of research on race and VET, drawing on a scoping exercise of the literature to evidence this. We conclude by offering a provisional analysis that identifies recent shifts in participation among BME groups, locating this in its socio-economic and historical context. Our analysis reaffirms that VET remains a significant educational site for BME groups, but it is a complex racialised site which makes the current neglect of race and VET in academic research deeply problematic." (authors' abstract ; BIBB-Doku)
Keywords: P 1.5 Migranten; S 1.4 Hochschulbildung; S 1.5 Weiterbildung; I 2.2.1 Westeuropa; Migrant; Ethnische Minderheit; Berufsausbildung; Hochschulbildung; Berufliche Mobilität; Benachteiligter Jugendlicher; Literaturanalyse; England